Endothelial AIP1 Regulates Vascular Remodeling by Suppressing NADPH Oxidase-2 - Zhang, Jiqin; Chen, Chaofei; Li, Li; Zhou, Huanjiao J.; Li, Fenghe; Zhang, Haifeng; Yu, Luyang; Chen, Yuxin; Min, Wang (Frontiers in Physiology, 2018)
Objective: AIP1 expression is downregulated in human atherosclerotic plaques and global deletion of AIP1 in mice exacerbates atherosclerosis in AopE-KO mouse models. However, the direct role of AIP1 in endothelium in vascular remodeling and associated vascular diseases have not been determined. Approach and Results: We used endothelial cell (EC)-specific AIP1-deficient (AIP1-ECKO) mice to define the role of AIP1 in vascular remodeling and intima-media thickening in a mouse carotid artery ligation model characterized by both neointimal hyperplasia and inward vessel remodeling. Compared to WT littermates, AIP1-ECKO mice had 2.2-fold larger intima area and 4.4-fold thicker intima as measured by intima/media ratio in arteries with more proliferating vascular smooth muscle cells (VSMCs) at week 2-4 post-injury. Increased reactive oxygen species (ROS) in endothelium at early time points induced inflammation and vessel dysfunction in AIP1-ECKO prior to VSMC accumulations. Moreover, knockdown of AIP1 in human EC enhanced ROS generation which was attenuated by co-silencing of NOX2. Mechanistically, AIP1 via its proline-rich region binds to the SH3 domain of cytosolic subunit p47phox to disrupt formation of an active NOX2 complex, attenuating ROS production. Conclusion: Our study supports that AIP1 regulates vascular remodeling with intima-media thickening by suppressing endothelial NOX2-dependent oxidative stress.